Adjustment to COVID-19 Lockdown Among Italian University Students: The Role of Concerns, Change in Peer and Family Relationships and in Learning Skills, Emotional, and Academic Self-Efficacy on Depressive Symptoms - Calandri, Emanuela; Graziano, Federica; Begotti, Tatiana; Cattelino, Elena; Gattino, Silvia; Rollero, Chiara; Fedi, Angela (Frontiers in Psychology, 2021)
In Italy strict containment measures against COVID-19 pandemic were implemented from March to May 2020 with home confinement and schools and universities closed. Students shifted to remote learning, experienced a forced isolation from peers and an increased sharing of time and spaces with the family. The influence of these aspects on the psychological adjustment of university students is largely unexplored. The aims of this study were: 1) to describe COVID-19 contagion concern, perceived changes in family and peer relationships and in learning skills, levels of emotional and academic self-efficacy and the presence of depressive symptoms; 2) to investigate the role of COVID-19 contagion concern, worsening in family and peer relationships and in learning skills on depressive symptoms and to explore the possible mediating role of emotional and academic self-efficacy; 3) to make an in-depth analysis of students’ perceptions of the pandemic and lockdown, paying particular attention to positive and negative aspects of remote learning. Data were collected from 296 Italian university students (aged 18-25 years; 83% girls) through an online survey by means of a snowball sampling methodology in May 2020. The questionnaire included closed and open-ended questions. Significant depressive symptoms were reported by 67% of participants. Contagion concerns were indirectly related to depressive symptoms through emotional self-efficacy. Worsening in learning skills was indirectly related to depressive symptoms through academic self-efficacy. Worsening in family relationships was directly related to depressive symptoms. Qualitative content analysis allowed a deep investigation of students’ perception about the effects of lockdown on different aspects of their life. Remote learning was evaluated as positive for its convenience, but many negative aspects were reported, mainly the lack of contact with teachers and classmates which had repercussions on learning processes and motivation. The negative effects on family relationships were mainly related to forced cohabitation and need of independence. Students were especially concerned about the reopening of universities, the possibility of studying abroad and future job opportunities. Strong feelings of sadness and uncertainty were reported. Results are discussed in relation to the need of preventive interventions for this specific population in view of universities reopening.